(untitled) (Research, Society and Development, 2019)
The present study aims to characterize in the literature the importance of nursing care management in the treatment and recovery of burn victims. Complete articles were selected considering as inclusion criteria articles of research on the subject of the care conduct to the patient victim of burn; available in full online; in the Portuguese language; and time cut from 2010 to 2018. We selected 06 articles for the corpus of the study. Evidencing the practices related to the care and contribution of the nursing team in the clinical evolution of these patients. It was identified how nursing care is important to the burned patient and the areas of care that encompass this perspective in the treatment and rehabilitation of the same. The assistance to the burn victim goes beyond the compliance with recommended protocols, it is necessary to seek new means of intervention, overcoming the barriers of clinical care where the main focus is the injury and not the patient as a whole.